Real and Nominal Effects of Monetary Shocks under Time-Varying Disagreement - Vania Esady (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper investigates the heterogeneity of monetary policy transmission under time-varying disagreement regimes using a threshold VAR. Empirically, I establish that during times of high disagreement, prices respond more sluggishly in response to monetary shocks. These stickier prices cause a flatter Phillips curve, leading to the empirical result that monetary policy has stronger real (output) effects in high disagreement periods. I develop a tractable theoretical model that show rationally inattentive price-setters produce this result. The model also links disagreement and uncertainty – two fundamentally different concepts, and bridges the results of this paper to the literature on state-dependent monetary transmission. The main result highlights a role for improved central bank communications that reduce disagreement among economic agents, which lessens output falls when implementing disinflationary monetary policies.
Keywords: E32; E52; E58; D83; 330; time-varying disagreement; monetary policy; threshold VAR; rational inattention